Negative electrode and lithium metal battery

By setting a porous structure layer with gradually decreasing electronic conductivity on the negative electrode of a lithium metal battery, the problem of lithium dendrite formation caused by uneven lithium ion deposition is solved, thereby improving the energy density and cycle life of the battery.

CN114512674BActive Publication Date: 2025-01-14BYD CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202011279926.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-16
Publication Date
2025-01-14
Estimated Expiration
2040-11-16

AI Technical Summary

Technical Problem

Uneven deposition of lithium ions during charge-discharge cycles in lithium metal anodes leads to the formation of lithium dendrites, causing battery short circuits and shortened cycle life.

Method used

A porous structure layer with gradually decreasing electronic conductivity along the direction away from the current collector is adopted. By setting a porous structure layer on the current collector, lithium ions are preferentially deposited in the porous structure layer close to the current collector, avoiding uneven deposition.

Benefits of technology

It effectively suppresses lithium dendrite formation, improves the energy density and cycle life of lithium metal batteries, reduces the risk of internal short circuits in batteries, and enhances the space utilization and rate performance of the negative electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114512674B_ABST
    Figure CN114512674B_ABST
Patent Text Reader

Abstract

The present application discloses a negative electrode plate and a metal lithium battery, wherein the negative electrode plate comprises a current collector and a porous structure layer disposed on at least one surface of the current collector; wherein the electronic conductivity of the porous structure layer gradually decreases in a direction away from the current collector. The present application adopts a porous structure layer whose electronic conductivity gradually decreases in a direction away from the current collector, so that lithium ions can be preferentially deposited in the porous structure layer close to the current collector, thereby achieving the purpose of guiding lithium ion deposition, avoiding the generation of lithium dendrites caused by uneven lithium ion deposition, and improving the energy density and cycle life of the metal lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application generally relates to the field of battery technology, and specifically to a negative electrode plate and a metal lithium battery. Background Art

[0002] Compared with traditional electrodes, metal lithium negative electrodes have higher theoretical specific capacity and lower electrochemical potential, which can significantly improve the mass energy density of existing battery systems. However, during the charge and discharge cycle of existing metal lithium negative electrodes, due to the uneven deposition of lithium ions on the surface of metal lithium, lithium dendrites are easily formed, resulting in battery short circuit and battery safety issues; in addition, the high electrochemical reaction activity of metal lithium makes it easy to react with the electrolyte to form SEI (solid electrolyte interface) film, and the volume change of the metal lithium negative electrode during the battery cycle will cause the SEI film generated on the negative electrode surface to rupture and expose the fresh metal lithium surface, which will further react with the electrolyte, consume active lithium, and affect the cycle life of the metal lithium battery. Summary of the invention

[0003] In view of the above-mentioned defects or deficiencies in the prior art, the present application hopes to provide a negative electrode plate and a metal lithium battery.

[0004] As a first aspect of the present application, the present application provides a negative electrode plate.

[0005] Preferably, the negative electrode plate comprises:

[0006] A current collector and a porous structure layer disposed on at least one surface of the current collector;

[0007] Wherein, the electronic conductivity of the porous structure layer gradually decreases in a direction away from the current collector.

[0008] Preferably, the porous structure layer is composed of n stacked sublayers, each of the sublayers has micropores and the electronic conductivity inside each sublayer is uniformly distributed; wherein n is an integer of 2 to 10; preferably, n is an integer of 2 to 3.

[0009] Preferably, each of the sub-layers is formed of different porous materials having different electronic conductivities; or,

[0010] Each of the sub-layers is formed of the same porous material with a different degree of oxidation or reduction; or,

[0011] Each of the sub-layers is formed by a composite of multiple porous materials with different electronic conductivities, wherein the sub-layers have different electronic conductivity distributions by changing the mass ratio of the high electronic conductivity component and the low electronic conductivity component in the porous material.

[0012] Preferably, the porous material is selected from at least one of carbon-based materials, silicon-based materials, high molecular polymers, metal nanowire materials and metal materials with a pore structure;

[0013] Among them, the carbon-based material is selected from at least one of graphene, porous carbon, carbon nanotubes and carbon fibers; the silicon-based material is selected from at least one of silicon, silicon nanowires, silicon dioxide and silicon monoxide; the metal nanowire material is selected from at least one of copper nanowires, silver nanowires and gold nanowires; the metal material with a pore structure is selected from at least one of copper, aluminum and nickel.

[0014] Preferably, the thickness of the sublayer is 100 nm to 50 μm, and the thickness of the porous structure layer is ≤100 μm.

[0015] Preferably, the pore sizes of the micropores in different sub-layers are the same or different, and the pore size of the micropores is ≤500 μm.

[0016] Preferably, the porous structure layer is filled with metallic lithium, and the metallic lithium is single substance lithium and / or lithium powder.

[0017] Preferably, the porous structure layer is also filled with a lithium-philic material, and the lithium-philic material is selected from LiNO 3 , at least one of zinc oxide, copper nanoparticles, and silicon nanoparticles.

[0018] Preferably, the current collector is selected from copper foil, titanium foil, nickel foil, iron foil or tin foil.

[0019] As a second aspect of the present application, the present application provides a metal lithium battery.

[0020] Preferably, the metal lithium battery comprises the negative electrode plate as described in the first aspect.

[0021] Beneficial effects of this application:

[0022] The present application adopts a porous structure layer whose electronic conductivity gradually decreases in the direction away from the current collector, so that lithium ions can be preferentially deposited in the porous structure layer close to the current collector, thereby achieving the purpose of guiding lithium ion deposition, avoiding the formation of lithium dendrites caused by uneven lithium ion deposition, and improving the energy density and cycle life of metal lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Other features, objects and advantages of the present application will become more apparent by reading the detailed description of non-limiting embodiments made with reference to the following drawings:

[0024] Figure 1 A structural side view of a negative electrode plate according to an embodiment of the present application;

[0025] Figure 2 This is a scanning electron microscope image of a porous structure layer of an embodiment of the present application. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention.

[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0028] It should be noted that the endpoints and any values ​​of the scope disclosed in this article are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, between the endpoint values ​​of each scope, between the endpoint values ​​of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. In the description of the present application, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or suggesting relative importance or implicitly indicating the quantity of the indicated technical features.

[0029] It should be noted that, unless otherwise specified, the raw materials involved in this application are all raw materials available on the market.

[0030] According to the first aspect of this application, please refer to Figure 1 , shows a negative electrode plate of a preferred embodiment of the present application, comprising: a current collector 1 and a porous structure layer 2 arranged on at least one surface of the current collector 1; wherein the electronic conductivity of the porous structure layer 2 gradually decreases in a direction away from the current collector 1.

[0031] In this embodiment, the current collector 1 is a conductive substrate commonly used in the art for collecting current, and the porous structure layer 2 is equivalent to a functional layer composited on the current collector 1, wherein the porous structure layer 2 is away from the surface of the current collector 1 and close to the battery separator.

[0032] When the negative electrode plate is used as the negative electrode of a metal lithium battery, the metal lithium embedded in the negative electrode plate can be provided by the positive electrode of the battery during the first charge; wherein, based on the electrochemical stripping-deposition reaction mechanism occurring at the metal lithium negative electrode, during the subsequent charging process of the battery, lithium ions are transported from the electrolyte side to the negative electrode side, obtain electrons on the surface of the metal lithium, and are deposited in the form of metal-lithium particles; during the discharge process, the metal lithium is oxidized into lithium ions and dissolved into the electrolyte; wherein, by providing a porous structure layer 2 on the current collector 1, the electronic conductivity of the porous structure layer 2 gradually decreases in the thickness direction of the current collector body 1, since the electronic conductivity of the porous structure layer 2 close to the current collector 1 is the highest, the ohmic overpotential at this location is lower during charging, and therefore the actual negative electrode potential applied here is relatively low, the nucleation driving force of the lithium ions is the largest, making it easier for the lithium ions to nucleate, thereby inducing the lithium ions to preferentially deposit on the porous structure layer close to the current collector 1, and avoiding the lithium ions from preferentially depositing on the surface of the porous structure layer 2 away from the current collector 1. As the charging process of the battery proceeds, due to the ohmic overpotential gradient, lithium ions are gradually deposited in the porous structure layer 2 from the direction close to the current collector 1 to the direction away from the current collector 1; this can not only prevent lithium ions from being preferentially deposited on the surface of the porous structure layer 2 away from the current collector 1, resulting in the formation of a large number of surface lithium dendrites after a small number of battery cycles, thereby accelerating the side reaction between metallic lithium and the electrolyte, resulting in a shorter battery life; it can also prevent lithium ions from preferentially depositing on the surface of the porous structure layer 2 away from the current collector 1 and then blocking the lower space thereof, resulting in the inability of lithium to fill the entire negative electrode plate; it can be seen from the above that the negative electrode plate of the present application can significantly alleviate the formation of lithium dendrites within a period of time or within the charge and discharge cycle, inhibit the significant electrode expansion of the negative electrode caused by the growth of lithium dendrites, and improve the cycle life of the metallic lithium negative electrode, and can make the deposition of lithium ions in the negative electrode uniform and dense, significantly improve the space utilization rate of the negative electrode and optimize the rate performance of the battery;

[0033] Among them, the porous structure layer 2 is equivalent to being divided into multiple regions in the thickness direction, and the region closer to the current collector 1 has a higher electronic conductivity; wherein, the porous structure layer 2 preferably has a random 3D pore structure to reserve space for lithium deposition and stripping. During lithium deposition or stripping, lithium ions can be easily transferred into or out of the porous structure layer 2. Since the electronic conductivity of the porous structure layer 2 is distributed in a regular pattern of gradually decreasing in the direction away from the current collector 1, the metallic lithium tends to grow in the porous structure layer close to the current collector 1 and gradually fill the pore structure of the entire porous structure layer 2; and due to the ultra-large specific surface area of ​​the porous structure layer 2, the negative electrode has a higher area capacity and can significantly improve its rate performance and service life; in addition, the pore structure of the porous structure layer can, on the one hand, suppress the large volume change of the metallic lithium negative electrode during the charge and discharge process, and increase the stable cycle capacity of the metallic lithium negative electrode; on the other hand, it can provide sufficient space for electrolyte penetration, thereby improving the performance of the metallic lithium battery using the negative electrode from the above-mentioned multiple aspects;

[0034] The porous structure layer may be located on one surface or both surfaces of the current collector 1 , thereby forming a negative electrode sheet having a single-sided structure or a double-sided structure.

[0035] Furthermore, in some preferred embodiments of the present application, the electronic conductivity of the porous structure layer 2 decreases gradually along the normal direction perpendicular to the current collector 1 .

[0036] Furthermore, in some preferred embodiments of the present application, the porous structure layer 2 is composed of n stacked sublayers, each of the sublayers has micropores and the electronic conductivity inside each sublayer is uniformly distributed; wherein n is an integer of 2 to 10.

[0037] Specifically, the porous structure layer 2 is composed of n stacked sublayers, wherein the electronic conductivity of the i-th sublayer is gradually reduced from the first layer adjacent to the current collector 1, so as to have n gradients of electronic conductivity distribution in the direction away from the current collector 1, wherein i is an integer from 1 to n. The gradient reduction described in the present application should be understood in a broad sense, and the difference in electronic conductivity between two adjacent sublayers from the first layer to the n-th layer may be equal or unequal. When the difference is unequal, the electronic conductivity may be reduced by multiples or irregularly by multiples from the first layer to the n-th layer.

[0038] The number of sublayers can be adjusted according to the actual needs of the battery. It is necessary to comprehensively consider the energy density of the negative electrode plate, the expected number of cycles of the metal lithium battery using the negative electrode plate, and the volume of the battery, so as to achieve the goal of improving the cycle life of the negative electrode while avoiding waste of internal space in the battery.

[0039] In some more preferred embodiments, n is an integer of 2 to 3, that is, the porous structure layer of the negative electrode plate of this embodiment is composed of 2 or 3 sublayers, thereby having 2 or 3 gradients of electronic conductivity distribution in the direction away from the current collector 1.

[0040] It is understandable that the porous structure layer 2 can present different electronic conductivity distributions by changing the stacking method of the sublayers with different electronic conductivities, such as gradient increase, periodic gradient decrease, periodic gradient increase, non-uniform mutation, etc. in the direction away from the current collector 1, so as to meet different needs.

[0041] Further, in some preferred embodiments of the present application, each of the sub-layers is formed of different porous materials having different electronic conductivities; or,

[0042] Each of the sub-layers is formed of the same porous material with a different degree of oxidation or reduction; or,

[0043] Each of the sub-layers is formed by a composite of multiple porous materials with different electronic conductivities, wherein the sub-layers have different electronic conductivity distributions by changing the mass ratio of the high electronic conductivity component and the low electronic conductivity component in the porous material.

[0044] In this embodiment, the porous material is defined as a material having a three-dimensional structure with pores inside the three-dimensional structure.

[0045] When different porous materials are used to form each sub-layer, for example, the first sub-layer 21 is composed of a 1 The second sublayer 22 is formed by a porous material. 2 The porous material is formed, and so on, the nth sublayer is composed of a n Formed by porous materials, a 1 The electronic conductivity of porous materials is greater than a 2 , a 2 The electronic conductivity is greater than a n ; wherein the first sublayer 21 is arranged adjacent to the current collector 1, and the nth sublayer is arranged starting from the first sublayer and in a direction perpendicular to the length direction of the current collector 1 at an end away from the current collector 1, so that a gradually decreasing electronic conductivity gradient is formed between the first sublayer and the nth sublayer;

[0046] When the same porous material is used to form each sublayer, the electronic conductivity of the porous material used to form each sublayer can be changed by changing the oxidation degree or reduction degree of the porous material, so that an electronic conductivity gradient is formed between the sublayers; wherein, the higher the oxidation degree of a porous material, such as a porous carbon material, the lower its electronic conductivity; the higher the reduction degree of a porous material, such as an oxidized porous carbon material, the higher its electronic conductivity;

[0047] When two or more porous materials are combined to form each sublayer, an electronic conductivity gradient can be formed between the sublayers by adjusting the mass ratio of components with high electronic conductivity and components with low electronic conductivity in the multiple porous materials forming each sublayer.

[0048] Further, in some preferred embodiments of the present application, the porous material is formed by at least one selected from carbon-based materials, silicon-based materials, high molecular polymers, metal nanowire materials and metal materials with a pore structure;

[0049] The metal material with a pore structure refers to a material in which holes are generated on a metal body in a sheet, block or other suitable shape by adopting a suitable method such as chemical or laser etching.

[0050] Further, in some preferred embodiments of the present application, the carbon-based material is selected from at least one of graphene, porous carbon, carbon nanotubes and carbon fibers; the porous carbon includes activated carbon; wherein, Figure 2 As shown, the porous structure layer formed by graphene has an obvious porous structure.

[0051] The silicon-based material is selected from at least one of silicon, silicon nanowires, silicon dioxide and silicon monoxide;

[0052] The high molecular polymer is selected from at least one of polyaniline, polyethylene oxide, polyimide, polyacrylic acid, polyethylene, polypropylene, polyacrylonitrile, polystyrene, polyvinyl fluoride, polyether ketone, polyester, polyvinylidene chloride, polytetrafluoroethylene, and polyethylene terephthalate;

[0053] The metal nanowire material is selected from at least one of copper nanowire, silver nanowire and gold nanowire;

[0054] The metal material having a pore structure is selected from at least one of copper, aluminum and nickel;

[0055] The above materials have good electrical conductivity and stability, and can form a stable porous structure layer skeleton;

[0056] Among them, taking carbon-based materials such as graphene and porous carbon as examples, their conductivity depends on the ratio of sp2-hybridized carbon atoms and sp3-hybridized carbon atoms in their structure. Sp2-hybridized carbon atoms are conductive, while sp3-hybridized carbon atoms are not conductive. Therefore, their electronic conductivity can be changed by adjusting the ratio of sp2 and sp3 hybridized structures in their structure; wherein, the ratio of sp2 and sp3 hybridized structures can be achieved by changing the degree of oxidation and reduction of the carbon-based material; for example, for graphene, by introducing oxidizing functional groups such as carboxyl, carbonyl, and hydroxyl, the ratio of sp3-hybridized carbon atoms on its surface is increased, thereby increasing its degree of oxidation and reducing its electronic conductivity; the introduction of oxidizing functional groups can be achieved by oxidizing graphene with an oxidizing agent for an appropriate time, and exemplary oxidizing agents include nitric acid, sulfuric acid, potassium permanganate, and the like;

[0057] Similarly, when a carbon-based material such as graphene oxide that has a large number of oxidized functional groups on its surface is used, the degree of reduction of the graphene oxide can be selectively controlled by treating the graphene oxide with a reducing agent for an appropriate period of time, thereby changing the electronic conductivity of the graphene oxide; exemplary reducing agents include unsymmetrical dimethylhydrazine, ascorbic acid, etc.; wherein, the method of changing the degree of oxidation or reduction of the carbon-based material can also be achieved by heating or microwaves, etc.;

[0058] When preparing each sublayer, the porous material can be dispersed in a suitable solvent or medium to form a uniform dispersion, and then the dispersion is coated on a plate or a container and cooled or filtered to form a hydrogel membrane.

[0059] Furthermore, in some preferred embodiments of the present application, the thickness of the sublayer is 100 nm to 50 μm, and the thickness of the porous structure layer is ≤100 μm.

[0060] The thickness of the sublayer affects the thickness of the porous structure layer, and the thickness of the porous structure layer affects the deposition effect of lithium ions and the stability of the porous skeleton. If the thickness is too small, it is not enough to form a relatively stable network structure, and if the thickness is too large, the thickness of the negative electrode plate will be too large, the battery weight will increase, and the cost of consumables will increase. Among them, the thickness of each sublayer can be the same or different.

[0061] Furthermore, in some preferred embodiments of the present application, the pore sizes of the micropores in different sub-layers are the same or different, and the pore size of the micropores is ≤500 μm.

[0062] If the pore size is too low, it will not provide enough space for lithium ions, resulting in low rate performance of the negative electrode, and then too low volume energy density of the battery; if the pore size is too high, the porous structure layer will be unstable and prone to collapse and damage during the preparation process or the cycle.

[0063] The pore size of the porous structure layer can be adjusted by regulating the pore size of each sub-layer micropore, thereby optimizing the rate performance of the negative electrode, so that under a relatively large polarization current, lithium ions are still preferentially deposited in the porous structure layer 2 close to the current collector 1;

[0064] The pore size adjustment can be achieved with the aid of a pore size control liquid, which is a mixture of two or more reagents with different boiling points. Under appropriate temperature treatment, one or more of the reagents can be selectively volatilized, while the other one or more reagents are retained in the micropores, thereby changing the pore size of the micropores. One optional pore size control method is to use the pore size control liquid to exchange the water in the hydrogel membrane, and to make some non-volatile reagents still exist in the micropores of the hydrogel membrane through drying or freeze drying, thereby retaining part of the original micropore structure, so that the pore size of the micropores is changed. Exemplary pore size control liquids include a mixed solution of deionized water and acetone, a mixed solution of acetone and dimethyl carbonate, a mixed solution of N,N-dimethylformamide and dimethyl carbonate, a solution containing one or more inorganic salts and a dispersible low-boiling point solvent, a suspension, an emulsion, such as a mixed solution of lithium nitrate and acetone, a mixed solution of lithium chloride and acetone, a mixed solution of lithium nitrate and N,N-dimethylformamide, etc., and may also include a mixed solution of any ionic liquid and a volatile solvent.

[0065] Among them, it is preferred that the pore size of the sublayer closer to the current collector is smaller. On the one hand, the ion flow rate is smaller closer to the current collector, and the required micropore size is also smaller, which can increase the space utilization rate; on the other hand, setting the pore size of the sublayer closer to the current collector body to be smaller can make the electronic conductivity of the sublayer closer to the current collector body higher, thereby guiding the lithium ions to preferentially begin to deposit in the sublayer close to the current collector.

[0066] Furthermore, in some preferred embodiments of the present application, the porous structure layer is filled with metallic lithium, and the metallic lithium is single substance lithium and / or lithium powder.

[0067] In the embodiment, filling the porous structure layer 2 with metallic lithium can be regarded as pre-depositing lithium in the negative electrode, that is, replenishing lithium. The filled metallic lithium as the active component of the metallic lithium negative electrode stably participates in the battery cycle, which can be used as a site for lithium deposition during charging, and can also make up for the consumption of active lithium in the battery cycle, thereby improving the battery cycle efficiency. In this embodiment, lithium powder refers to powder particles with a protective layer on the surface of single lithium, and the protective layer is composed of lithium carbonate, lithium fluoride, lithium metasilicate, lithium orthosilicate, lithium phosphate, lithium sulfate, LiTi 2 (PO 4 ) 3 , Li 14 Zn(GeO 4 ) 4 , Li7 La 3 Zr 2 O 12 , paraffin, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, polysiloxane, polyacrylonitrile, polypropylene carbonate, polymethyl methacrylate, polyvinyl chloride and other coating materials, which protect the single lithium coated inside the protective layer. When the lithium powder is used, the protective layer breaks and releases the single lithium;

[0068] Among them, the metallic lithium can be absorbed into the porous structure layer 2 by capillary action in a molten state, and the porous structure layer 2 provides a stable framework for the deposition and removal of metallic lithium, significantly reducing the volume change caused by the metallic lithium during the cycle; wherein, the filling amount of metallic lithium is 0.5 to 10 times the capacity of the positive electrode of the battery, and this filling amount can ensure good cycle performance of the battery, and while filling the porous structure layer 2, the entire porous structure layer 2 is not completely filled, which is conducive to the subsequent infiltration of the negative electrode plate by the electrolyte;

[0069] Optionally, the method of filling metallic lithium can be adopted in the following two ways:

[0070] The first method is a melting method: the current collector stacked with the porous structure layer 2 and the metal lithium are treated at high temperature together, the metal lithium melts into a flowable liquid at high temperature, and the metal lithium is adsorbed in the porous structure layer 2 by siphoning;

[0071] The second method is electrochemical deposition: an assembled half-cell can be used to electrochemically deposit metallic lithium in the porous structure layer 2, generally with a lithium sheet as the counter electrode and a corresponding current collector stacked with the porous structure layer 2 as the working electrode.

[0072] Furthermore, in some preferred embodiments of the present application, the porous structure layer is further provided with a lithium-philic material for providing nucleation sites to promote lithium deposition, and the lithium-philic material is selected from LiNO 3 , at least one of zinc oxide, copper nanoparticles, and silicon nanoparticles.

[0073] The above-mentioned lithium-philic material can induce lithium ion nucleation, so that the effective specific surface area of ​​the negative electrode plate can be fully utilized during the lithium deposition process, achieving dendrite-free lithium deposition and long cycle life; wherein the addition amount of the above-mentioned lithium-philic material does not exceed 10% of the total mass of the porous material forming the porous structure layer.

[0074] Furthermore, in some preferred embodiments of the present application, the current collector is a metal foil commonly used in the art, including but not limited to copper foil, titanium foil, nickel foil, iron foil or tin foil.

[0075] Among them, a method for preparing the negative electrode sheet of the present application may include the following steps:

[0076] preparing sublayers with different electronic conductivities, each of the sublayers having micropores and the electronic conductivity inside each of the sublayers being uniformly distributed;

[0077] On at least one surface of a current collector, the sublayers are stacked and fixed to the current collector in an order in which the electronic conductivity gradually decreases in a direction away from the current collector;

[0078] In this embodiment, the sublayers can be fixed on the current collector by hot pressing, filtration or bonding with an adhesive; wherein, when hot pressing or filtration is used, the sublayers are first stacked on the current collector in the order of gradually decreasing electronic conductivity in the direction away from the current collector, and then the current collector stacked with the sublayers is hot pressed or filtered, so that each sublayer is fixed on the current collector, wherein the temperature of the hot pressing treatment can be 80 to 150°C, and the pressure can be 0.5 to 2.0MPa; when adhesive bonding is used, after the first sublayer is bonded and fixed to the current collector, the second sublayer is stacked and bonded on the first sublayer, and so on, until a negative electrode sheet with a porous structure layer of appropriate thickness is obtained.

[0079] A more specific preparation process can be as follows:

[0080] First, prepare the first sublayer, the electronic conductivity of the first sublayer is σ 1 ;

[0081] Prepare the second sublayer, the electronic conductivity of the second sublayer is σ 2 ;

[0082] By analogy, the i-th sublayer is prepared, and the electronic conductivity of the i-th sublayer is σ i ;

[0083] Until the nth sublayer is prepared, the electronic conductivity of the nth sublayer is σ n ;

[0084] Among them, σ 1 >σ 2 >…>σ i >…>σ n

[0085] Wherein, n is an integer greater than or equal to 2, preferably an integer from 2 to 10, more preferably 2 or 3;

[0086] wherein each sublayer has micropores;

[0087] Sequentially stacking the first to nth layers on at least one surface of the current collector body in a direction perpendicular to the normal line of the current collector body to form a porous structure layer including n sublayers on at least one surface of the current collector body;

[0088] The negative electrode sheet of the present application is obtained by subjecting the current collector body stacked with the porous structure layer to high temperature and high pressure hot pressing treatment so that each sublayer is densely connected.

[0089] Furthermore, before obtaining sublayers with different electronic conductivities and stacking the sublayers, a step of adjusting the pore size of the micropores of each sublayer is included. Specifically, after each sublayer is prepared into a hydrogel membrane, the pore size of the micropores of each sublayer can be adjusted by a pore size controlling liquid, thereby obtaining a porous structure layer with the same or different pore size distribution.

[0090] Furthermore, after obtaining the negative electrode plate, the method further includes filling metallic lithium in the micropores, wherein the method of filling metallic lithium in the micropores can adopt the melting method or electrochemical deposition method as described above, so as to achieve the loading or filling of metallic lithium in the porous structure layer.

[0091] According to a second aspect of the present application, the present application provides a metal lithium battery, which includes the negative electrode plate as described above.

[0092] Among them, in some embodiments, the metal lithium battery of the present application can be an all-solid-state battery, which includes not only a negative electrode plate but also a positive electrode plate; in other embodiments, the metal lithium battery of the present application can be a semi-solid-state battery or a liquid battery, which includes not only a negative electrode plate but also a positive electrode plate, a separator located between the negative electrode plate and the positive electrode plate, and an electrolyte.

[0093] Exemplarily, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer includes a positive electrode active substance, a conductive agent, an adhesive, etc. The positive electrode sheet is prepared by an existing preparation method, for example, a slurry containing a positive electrode active substance, a conductive agent, an adhesive and a solvent is coated on the positive electrode current collector, and then subjected to a roller pressing treatment of 0 to 5 MPa after drying; wherein the positive electrode current collector may include but is not limited to a metal foil (for example, an aluminum foil, etc.), and the positive electrode active substance is selected from LiCoO 2 、LiNiO 2 、LiCo x Ni 1-x O 2 (0≤x≤1), LiCo x Ni 1-x-y Al y O 2 (0≤x≤1, 0≤y≤1), LiMn 2 O 4 、LiFe x Mn y M z O 4(M is at least one of Al, Mg, Ga, Cr, Co, Ni, Cu, Zn or Mo, 0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1), Li 1+x L 1-y-z M y N z O 2 (L, M, N are at least one of Li, Co, Mn, Ni, Fe, Al, Mg, Ga, Ti, Cr, Cu, Zn, Mo, F, I, S, B, -0.1≤x≤0.2, 0≤y≤1, 0≤z≤1, 0≤y+z≤1), LiFePO 4 , Li 3 V 2 (PO 4 ) 3 , Li 3 V 3 (PO 4 ) 3 、LiVPO 4 F. Li 2 CuO 2 , Li 5 FeO 4 , and metal sulfides and oxides such as V 2 S 3 ,FeS,FeS 2 、LiMS x (M is at least one transition metal element such as Fe, Ni, Cu, Mo, etc., 1≤x≤2.5), TiO 2 Cr 3 O 8 、V 2 O 5 、MnO 2 At least one of the groups consisting of, etc., preferably the positive electrode particle size range is between 100nm-500μm; wherein the binder is a common binder for positive electrodes, including but not limited to one or more of fluorine-containing resins and polyolefin compounds such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE) and styrene-butadiene rubber (SBR); wherein the conductive agent is a common conductive agent for positive electrodes, such as acetylene black, carbon nanotubes, carbon fibers, carbon black, etc.; wherein the solvent can be selected from one or more of N-methylpyrrolidone (NMP), water, ethanol, and acetone; wherein, based on the weight of the positive electrode active material layer, the content of the binder is 0.01-10wt%, preferably 0.02-5wt%; the content of the conductive agent is 0.1-20wt%, preferably 1-10wt%; the amount of the solvent is generally 50-400wt%.

[0094] Exemplarily, the electrolyte comprises a solvent and a lithium salt, wherein the solvent has one or more of the following groups: an ether group, a nitrile group, a cyanate group, a fluoroester group, a tetrazolyl group, a fluorosulfonyl group, a chlorosulfonyl group, a nitro group, a carbonate group, a dicarbonate group, a nitrate group, a fluoroamide group, a diketone group, an azole group, and a triazine group; and the lithium salt is LiPF 6 、LiAsF 6 、LiClO 4 , LiBF 6 、LiN(CF 3 SO 3 ) 2 、LiCF 3 SO 3 、LiC(CF 3 SO 3 ) 2 and LiN(C 4 F 9 SO 2 )(CF 3 SO 3 )

[0095] Illustratively, when the metal lithium battery of the present application is a semi-solid battery or a liquid battery, the separator can be selected from polyethylene, polypropylene, polyvinylidene fluoride, and a multilayer composite film of polyethylene, polypropylene, and polyvinylidene fluoride.

[0096] Exemplarily, the metal lithium battery is further packaged on the outside, such as an aluminum-plastic film, a stainless steel cylinder, a square aluminum shell, etc.

[0097] Among them, the metal lithium battery of the present application can be in the form of a button battery or a laminated battery, and can be a full battery or a half battery; the specific preparation method of the metal lithium battery is not particularly limited and is a conventional preparation method of metal lithium batteries in the art.

[0098] Example 1

[0099] (I) Preparation of negative electrode sheet

[0100] 1 g of graphene oxide and 0.2 g of UDMH were mixed, dissolved in 800 ml of distilled water under stirring and ultrasonically dispersed for 20 min, 0.2 g of 35% by mass aqueous ammonia was added to the mixed solution to adjust the pH to 7-9, and reacted in a water bath at 100 degrees Celsius for 120 min;

[0101] The dispersion was naturally cooled to room temperature and filtered to obtain a graphene oxide hydrogel film;

[0102] The graphene oxide hydrogel film was immersed in a 10% by mass lithium nitrate aqueous solution for 12 hours to replace the water in the hydrogel with a 10% by mass lithium nitrate solution; then dried at 100 degrees Celsius for 24 hours to obtain the first sublayer prepared by reducing graphene oxide. The electronic conductivity of the first sublayer was measured to be 3.6×10 4 S / cm, average pore size of 6nm, thickness of 10μm;

[0103] The preparation of the second sublayer is similar to that of the first sublayer, except that the water bath reaction time is 60 min. The electronic conductivity of the second sublayer is 1.6×10 3 S / cm, average pore size of 6nm, thickness of 10μm;

[0104] The preparation of the third sublayer is similar to that of the first sublayer, except that the water bath reaction time is 30 min. The electronic conductivity of the third sublayer is 370 S / cm, the average pore size is 6 nm, and the thickness is 10 μm.

[0105] The above-mentioned water bath heating time determines the degree of reduction and the number of defects of graphene. The longer the time, the higher the degree of reduction and the higher the electronic conductivity.

[0106] The first sublayer, the second sublayer and the third sublayer are sequentially placed on the copper foil, and then hot pressed at 100° C. and 0.8 MPa to obtain a negative electrode sheet with an electronic conductivity gradient arranged in the order of copper foil-first sublayer-second sublayer-third sublayer; wherein the thickness of the copper foil is 5 μm;

[0107] Then the negative electrode obtained above is heated together with lithium powder to 200 degrees Celsius to control the surface capacity of metal lithium to 5 mAh / cm 2 After all the lithium is integrated into the porous structure layer and cooled to room temperature, it is cut into 480mm (length) × 45mm (width) as a negative electrode sheet for use.

[0108] (II) Preparation of positive electrode sheet

[0109] 8.8 g LiCoO 2 The positive electrode active material (88 wt%), 0.3 g of the binder PVDF (3 wt%), 0.2 g of acetylene black (2 wt%), and 0.2 g of the conductive agent carbon nanotube (2 wt%) were added to 15 g of the solvent NMP (nitromethylpyrrolidone), and then stirred in a mixer to form a stable and uniform positive electrode slurry;

[0110] The positive electrode slurry is uniformly and intermittently coated on both sides of an aluminum foil (aluminum foil size: width 45 mm, length 480 mm, thickness 16 μm), and then dried at 393 K. After being pressed by a roller press, a positive electrode sheet is obtained for use.

[0111] (III) Preparation of CEA lithium metal full battery

[0112] In a glove box, the negative electrode plate obtained in the above step (i) and the positive electrode plate obtained in the step (ii) are aligned and placed in an aluminum-plastic film, a layer of diaphragm (PE) is inserted in the middle, and 4M DME electrolyte is injected at an injection volume of 3g / Ah, and then the aluminum-plastic film is used for vacuum sealing to obtain a metal lithium full battery.

[0113] Example 2

[0114] A metal lithium battery was prepared according to the method of Example 1, except that the preparation of the negative electrode sheet was different;

[0115] The preparation of the negative electrode sheet of this embodiment is as follows:

[0116] 1 g of graphene was dissolved in 800 mL of distilled water, ultrasonically dispersed for 20 min, and reacted in a water bath at 100 °C for 120 min;

[0117] The dispersion was naturally cooled to room temperature and filtered to obtain a graphene oxide hydrogel film;

[0118] The graphene oxide hydrogel film was immersed in a 10% by mass lithium nitrate aqueous solution for 12 hours to replace the water in the hydrogel with a 10% by mass lithium nitrate solution; liquid nitrogen and a freeze dryer were used for freeze drying to obtain a three-dimensional network-like first sublayer prepared by graphene. The electronic conductivity of the first sublayer was measured to be 2.06 x 10 2 S / cm, the average pore size is about 5 μm, and the thickness is about 20 μm;

[0119] Take 300ml of 1mol / L HCl aqueous solution, add 3g of 10% polyaniline aqueous solution and 0.3g of graphene, stir evenly, take out and place at room temperature, filter and dry, and obtain the second sublayer. It is measured that the electronic conductivity of the second sublayer is 2.29S / cm, the average pore size is 10μm, and the thickness is about 35μm;

[0120] The first sublayer and the second sublayer are sequentially placed on the copper foil, and then hot pressed at 80° C. and 0.5 MPa to obtain a negative electrode sheet with an electronic conductivity gradient arranged in the order of copper foil-first sublayer-second sublayer; wherein the thickness of the copper foil is 5 μm;

[0121] Then the negative electrode obtained above is heated together with lithium powder to 200 degrees Celsius to control the surface capacity of metal lithium to 5 mAh / cm 2 After all the lithium is integrated into the porous structure layer and cooled to room temperature, it is cut into 480mm (length) × 45mm (width) as a negative electrode sheet for use.

[0122] Comparative Example 1

[0123] A metal lithium battery was prepared according to the method of Example 1, except that the negative electrode sheet was different. The preparation of the negative electrode sheet of this comparative example was as follows:

[0124] A 25-micron-thick lithium metal single substance is deposited on a copper foil and then cut into 480 mm (length) × 45 mm (width) as a negative electrode sheet; wherein the thickness of the copper foil is 5 μm.

[0125] Comparative Example 2

[0126] A metal lithium battery was prepared according to the method of Example 2, except that the negative electrode sheet was different; the preparation of the negative electrode sheet of this comparative example was as follows:

[0127] The first sub-layer prepared in Example 1 is placed on the copper foil, and then hot-pressed to obtain a negative electrode sheet having a composite structure of copper foil-first sub-layer; wherein the thickness of the copper foil is 5 μm;

[0128] Then the negative electrode obtained above is heated together with lithium powder to 200 degrees Celsius to control the surface capacity of metal lithium to 5 mAh / cm 2 After all the lithium is integrated into the first sublayer and cooled to room temperature, it is cut into 480mm (length) × 45mm (width) as the negative electrode sheet.

[0129] Battery performance test

[0130] (I) Battery cycle performance test

[0131] The metal lithium batteries obtained in the above examples and comparative examples were tested for battery cycle performance, and the test method was as follows:

[0132] Take 20 batteries prepared in each embodiment and comparative example, and perform charge-discharge cycle test at 0.5C on LAND CT2001C secondary battery performance test device under 298±1K conditions, with the following steps: leave for 10 minutes; charge at constant current until 4.4V is cut off; leave for 10 minutes; discharge at constant current until 3V is one cycle. Repeat this step, and when the battery capacity is lower than 80% of the initial discharge capacity during the cycle, the cycle is terminated. The number of cycles is the cycle life of the battery, and the average value is taken for each group;

[0133] (II) Negative electrode thickness expansion change test

[0134] Under the condition of 298±1K, the batteries prepared in each embodiment and comparative example were subjected to a charge and discharge cycle test at 0.5C, and the steps were as follows: stand for 10 minutes; charge at a constant current until 4.4V was cut off; stand for 10 minutes; discharge at a constant current until 3V, which is 1 cycle. Repeat this step, and after 1000 cycles, disassemble the battery and take out its negative electrode sheet. Cut the negative electrode sheet to expose the cross section, and polish the cross section with an ion cutter, and measure the change in the thickness of the negative electrode sheet with a screw micrometer.

[0135] The experimental results are shown in the following table:

[0136]

[0137]

[0138] It can be seen from the battery cycle performance test that the battery of the embodiment shows a more excellent cycle performance than that of the comparative example, indicating that the negative electrode plate of the present application has a better cycle life.

[0139] Among them, the negative electrode plate of Comparative Example 2 has the same electronic conductivity at each location of the porous structure layer, resulting in the same overpotential of the entire porous structure layer acting on the electrode surface, so the original driving force for the deposition of lithium ions in the porous structure layer is the same. Since the lithium ions near the diaphragm are more abundant, the lithium ions have lower nucleation energy on the surface of the porous structure layer near the diaphragm, and the lithium ions are preferentially deposited on the surface of the porous structure layer near the diaphragm to form lithium dendrites; the growth of lithium dendrites is self-reinforcing. Once formed, new lithium ions will be more inclined to deposit at the lithium dendrites, thereby accelerating The formation of lithium dendrites is aggravated. In addition, the volume of metal lithium changes greatly during the charge and discharge process. The change in the thickness of metal lithium leads to the movement of the metal lithium interface. During the large volume change, SEI breaks to expose a new metal lithium surface. Lithium ions are more likely to deposit on this surface, which also aggravates the formation of lithium dendrites. On the one hand, the continuous growth of lithium dendrites will pierce the diaphragm, causing an internal short circuit in the metal lithium battery and a thermal runaway explosion. On the other hand, lithium dendrites break during the dissolution process to form "dead lithium", causing a decrease in the negative electrode capacity, which affects the cycle life of the battery from multiple aspects.

[0140] The present application adopts a porous structure layer in which the electronic conductivity decreases gradually in the vertical direction away from the current collector, so that lithium ions can be preferentially deposited in the porous structure layer close to the current collector, thereby achieving lithium deposition without lithium dendrites within a period of time or within the charge and discharge cycle, thereby improving the cycle life of the metal lithium battery.

[0141] By measuring the thickness of the negative electrode plates of the battery after 1000 cycles, it was found that the thickness of the negative electrode plates of Examples 1 and 2 did not increase significantly compared with the thickness of the plates before cycling (i.e., the initial plate thickness), and the surface of the plates after cycling was relatively flat and smooth, and still maintained a dense structure, while the thickness of the negative electrode plates of Comparative Examples 1 and 2 increased significantly compared with the initial plate thickness, and a large number of irregular deposits were observed on the surface of the plates, indicating that the negative electrode plates of the present application can facilitate the stable release and deposition of lithium ions on the electrode, reduce the formation of surface dendrites and reduce side reactions, and can significantly inhibit the expansion of the negative electrode thickness.

[0142] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

Claims

1. A negative electrode plate, characterized in that: include: A current collector and a porous structure layer disposed on at least one surface of the current collector; wherein the electronic conductivity of the porous structure layer gradually decreases in a direction away from the current collector; The porous structure layer is composed of n stacked sublayers, and the sublayers are made of hydrogel films formed by porous materials; the sublayers are fixed on the current collector by hot pressing, filtration or bonding with adhesives to form the negative electrode sheet; the pore size control liquid is used to exchange the water in the hydrogel film to adjust the micropore size of the sublayer; The porous structure layer is filled with metallic lithium, which is lithium powder.

2. The negative electrode sheet according to claim 1, characterized in that: Each of the sub-layers has micropores and the electronic conductivity inside each of the sub-layers is uniformly distributed; wherein n is an integer of 2 to 10.

3. The negative electrode sheet according to claim 2, characterized in that: n is an integer from 2 to 3.

4. The negative electrode sheet according to claim 2, characterized in that: Each of the sub-layers is formed of a different porous material having a different electronic conductivity; or, Each of the sub-layers is formed of the same porous material with a different degree of oxidation or reduction; or, Each of the sub-layers is formed by a composite of multiple porous materials with different electronic conductivities, wherein the sub-layers have different electronic conductivity distributions by changing the mass ratio of the high electronic conductivity component and the low electronic conductivity component in the porous material.

5. The negative electrode sheet according to claim 4, characterized in that: The porous material is selected from at least one of a carbon-based material, a silicon-based material, a high molecular polymer, a metal nanowire material and a metal material with a pore structure.

6. The negative electrode sheet according to claim 5, characterized in that: The carbon-based material is selected from at least one of graphene, porous carbon, carbon nanotubes and carbon fibers; the silicon-based material is selected from at least one of silicon, silicon nanowires, silicon dioxide and silicon monoxide; the metal nanowire material is selected from at least one of copper nanowires, silver nanowires and gold nanowires; the metal material with a pore structure is selected from at least one of copper, aluminum and nickel.

7. The negative electrode sheet according to claim 2, characterized in that: The thickness of the sublayer is 100nm~50µm, and the thickness of the porous structure layer is ≤100µm.

8. The negative electrode sheet according to claim 2, characterized in that: The pore sizes of the micropores in different sub-layers are the same or different, and the pore size of the micropores is ≤500µm.

9. The negative electrode sheet according to claim 1, characterized in that: The metallic lithium also includes single substance lithium.

10. The negative electrode sheet according to claim 1, characterized in that: The porous structure layer is also filled with a lithium-philic material, and the lithium-philic material is selected from at least one of LiNO3, zinc oxide, copper nanoparticles, and silicon nanoparticles.

11. A metal lithium battery, characterized in that: Comprising the negative electrode sheet as described in any one of claims 1 to 10.

Citation Information

Patent Citations

  • Negative electrode sheet, electrochemical device comprising negative electrode sheet and electronic device

    CN109994739A

  • Metal lithium negative electrode for secondary battery, preparation method and application thereof

    CN110010852A

  • Negative pole piece and use its cylindrical lithium ion battery

    CN204947011U

  • Secondary battery negative current collector and lithium secondary battery using it

    JP1999003713A

  • Electrode Having Electrode Material Layer With Uniform Porous Ratio

    KR1020150014800A